Combinatorial image analysis : 19th International Workshop, IWCIA 2018, Porto, Portugal, November 22-24, 2018, Proceedings /: 19th International Workshop, IWCIA 2018, Porto, Portugal, November 22-24, 2018, Proceedings. (2018) - Unknown
No abstract available